Campaña social como instrumento para sensibilizar sobre la salud mental en adolescentes de la U.E. Madres Gertrudis en el Cantón Cevallos - Guzmán Mayorga, Marco Vinicio (2023)
Mental health in adolescents is a fundamental part of their development as a person, if there is no care it can have serious consequences on a daily basis, where the effects of poor mental health are most frequently detected is in educational institutions since they spend the most time there, therefore, through the development of this project, the development of a social campaign as a tool to raise awareness among adolescents, so they take care of their mental health and support those who need it. For this reason, research and data collection was carried out on factors affecting the mental health of adolescents, using a qualitative and quantitative approach, with interviews and surveys to determine the level of ignorance on the subject, as well as to ascertain the opinion on how important it is to know about mental health in adolescence.In this way, the information collected will serve to generate strategies for the development of appropriate proposals for the development of the social campaign that will be disseminated by the most appropriate means to reach the target audience.